2021
DOI: 10.3389/fphar.2021.733577
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Pilot Study of Changes in Global DNA Methylation in Patients Undergoing Major Breast Surgery Under Opioid-Based General Anesthesia

Abstract: This study aimed to investigate DNA methylation levels in patients undergoing major breast surgery under opioid-based general anesthesia. Blood samples were collected from eleven enrolled patients, before, during and after anesthesia. PBMC were isolated and global DNA methylation levels as well as DNA methyltransferase (DNMT) and cytokine gene expression were assessed. DNA methylation levels significantly declined by 26%, reversing the direction after the end of surgery. Likewise, DNMT1a mRNA expression was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Total RNA was extracted according to the method of Chomczynski and Sacchi (2006). Each sample was subjected to DNAse treatment and converted to cDNA with the GeneAmp RNA PCR kit (Life Technologies Italia, Italy) as previously described (Caputi et al, 2019(Caputi et al, , 2021. The qRT-PCR analysis was performed on a StepOne Real-Time PCR System (Life Technologies, Italy) using the SYBR Green PCR MasterMix (Life Technologies, Italy).…”
Section: Rna Extraction and Gene Expression Analysis By Real-time Qpcrmentioning
confidence: 99%
“…Total RNA was extracted according to the method of Chomczynski and Sacchi (2006). Each sample was subjected to DNAse treatment and converted to cDNA with the GeneAmp RNA PCR kit (Life Technologies Italia, Italy) as previously described (Caputi et al, 2019(Caputi et al, , 2021. The qRT-PCR analysis was performed on a StepOne Real-Time PCR System (Life Technologies, Italy) using the SYBR Green PCR MasterMix (Life Technologies, Italy).…”
Section: Rna Extraction and Gene Expression Analysis By Real-time Qpcrmentioning
confidence: 99%
“…However, similar results were observed in the processes of aging and carcinogenesis. 9 , 38 Indeed, studies on PND have also observed global DNA hypomethylation, 11 , 39 and DNA hypermethylation of several genes (e.g. glucocorticoid receptor, Arc, Bdnf, Reln, PSD‐95 ), 10 , 40 , 41 indicating that the global DNA methylation status did not necessarily reflect the methylation of specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies thus far have evaluated post-operative acute epigenetic changes for any kind of surgery (except bariatric surgery). [13][14][15] Studies have shown alterations in gene-speci c and global DNA methylation levels during and after the surgery; however, no consistent trend has been reported. [13][14][15] Again, no study has explored long-term and persistent epigenetic changes after the surgery (except in the case of bariatric surgery).…”
Section: Discussionmentioning
confidence: 99%